2020
DOI: 10.3390/ijerph17155370
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Relationships with Smartphones of Spanish and Colombian University Students

Abstract: The presence of smartphones in the lives of the population in general, and of youth in particular, is evident, and is derived from elements such as the diversity of prices as well as the ease of access of all the resources that can be reached through the internet. With the use of a descriptive approach using a quantitative poll, the objective of the present study was to discover the opinions of university students in Spain and Colombia about smartphone use, as well as the consequences of its use, and if this u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
2
7
0
7
Order By: Relevance
“…The proof of this is that they did not consider the time they devoted to it to be excessive or to have increased over the past year. This same perspective was identified in the study by Marín-Díaz et al [41], Ruiz [84], and Marín et al [85], in which the participants were reluctant to classify their pattern of use as excessive or maladaptive. One possible explanation for this might lie in the device's increasing integration into their daily lives, which may lead them to normalise its use.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The proof of this is that they did not consider the time they devoted to it to be excessive or to have increased over the past year. This same perspective was identified in the study by Marín-Díaz et al [41], Ruiz [84], and Marín et al [85], in which the participants were reluctant to classify their pattern of use as excessive or maladaptive. One possible explanation for this might lie in the device's increasing integration into their daily lives, which may lead them to normalise its use.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, the study by Leonardi, Leonardi and Hudson [74] revealed that, compared to Latin American and European users, those from the United States were more likely to use the device to escape loneliness and to reach out to other people. Marín-Díaz et al [41], meanwhile, confirmed the low tendency displayed by Spanish and Colombian students to classify their use of the device as excessive, implying that they consider their patterns of use to fall within normality. Similarly, the results of the study by Višnjic et al [75] of Italian and Serbian students could not establish a possible relationship between smartphone use and depression problems.…”
Section: Problematic Smartphone Use Among University Studentsmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, the main aim was to cover health and education approaches in the context of these problems, which has partially been achieved, as the majority of papers (74%) included both approaches. However, half of the papers (54%) were studies undertaken in educational settings (i.e., high schools [ 14 , 18 ], universities [ 12 , 13 ]) with a health purpose, such as to adapt a diagnostic tool [ 12 , 13 , 20 , 21 , 32 , 37 , 45 ] or to study psychological mechanisms or comorbid problems which affect or mediate these problems to be used in prevention and treatment plans [ 17 , 22 , 23 , 24 , 25 , 46 ]. Only a few studies (20%) were conducted in health settings (i.e., hospitals [ 44 ] or health centres [ 33 ]) or were health reviews about these problems [ 46 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all works were empirical (90%) with quantitative studies (only two mixed methods and no qualitative ones). Still there are a fifth of the papers in the Special Issue which are psychometric studies, in which usually cultural validations of diagnostic tools have been undertaken, such as the Spanish and Colombian Mobile Phone Problematic Use Scale for Adolescents (MPPUSA [ 13 ]), or the Problematic Pornography Consumption Scale (PPCS [ 37 ]), which shows the interest to scientifically validate existing measures on problematic use of smartphones, gaming and pornography across cultures [ 51 , 52 ]. This long tradition in psychometrics in the field is probably due to the global phenomena related to the addictive uses of technologies world-wide, and the cross-cultural interest in these common problems in young populations [ 53 ].…”
Section: Discussionmentioning
confidence: 99%